THE REPRESENTATION OF SOCIAL IDENTITY IN THE FILM JAKARTA VS EVERYBODY: A JOHN FISKE SEMIOTIC ANALYSIS - Hafis Hasym; Elis Zuliati Anis (SOSIOEDUKASI, 2026)
This study examines the representation of social identity through the character of Dom in Jakarta vs Everybody (2020) using John Fiske's semiotic framework. The film portrays urban life through the experiences of a migrant youth confronted with economic hardship, social alienation, and unequal power relations in Jakarta. Employing a qualitative interpretive approach, the study analyzes four key scenes depicting bodily control, involvement in criminal social networks, criminal activities in urban public spaces, and the protagonist's identity crisis. The analysis is conducted at the levels of reality, representation, and ideology. The findings indicate that Dom's social identity is constructed as a marginalized identity that is continuously negotiated within the pressures of urban life. Visual and narrative elements reveal how economic precarity, power relations, and the urban social environment shape the protagonist's engagement in exploitative social relationships as a survival strategy. The film further represents urban criminality not merely as individual deviance but as a consequence of broader social inequalities. These findings suggest that film serves as a cultural medium through which meanings of marginalization, social identity, and survival in contemporary urban contexts are constructed.